The exploitation of black women under The Theory of Work-Value - Araujo, Lorraine Marie Farias de (Argumentum, 2023)
This article explains the exploitation of black women under the labour theory of value. It analyses the novel Eu, Tituba: bruxa negra de Salem, by Maryse Condé, employing the Marxian method as a theoretical framework. It contests that, bourgeois society arose through the systematic and collective rape of enslaved women for the reproduction of the workforce, extraction of surplus value, and capital accumulation. This reverberates in today’s attempts to downgrade the humanity of black (or racialised) women, resulting in worse working conditions and greater exposure to patriarchal violence due to racist dehumanisation. Keywords: Black woman. Exploitation. Racism. Dehumanisation. Labour Theory of Value.